2019
DOI: 10.3892/ijo.2019.4846
|View full text |Cite
|
Sign up to set email alerts
|

In vitro attenuation of classic metastatic melanoma‑related features by highly diluted natural complexes: Molecular and functional analyses

Abstract: Metastasis is responsible for the majority of deaths among patients with malignant melanoma. Despite recent advances, the majority of current and modern therapies are ineffective and/or financially unfeasible. Thus, in this study, we investigated two low-cost highly-diluted natural complexes (HDNCs) that have been shown to be effective against malignant melanoma in a murine model in vivo. The aim of this study was to determine the mechanisms through which these HDNCs directly affect melanoma cells, either alon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 78 publications
0
4
0
Order By: Relevance
“…Further, it would increase the possibility of replacing some toxic drugs in modern medicine with their cheap non-toxic potentized forms. It may even support and widen the scope of the emerging strategy to find safer and more effective integrative treatments for specific cancers (Gonçalves et al, 2019;Bhattacharya and Zhang, 2015;Bell et al, 2014).…”
Section: Emerging Experimental Support and Possibility Of Verification Of The Proposed Theorymentioning
confidence: 99%
“…Further, it would increase the possibility of replacing some toxic drugs in modern medicine with their cheap non-toxic potentized forms. It may even support and widen the scope of the emerging strategy to find safer and more effective integrative treatments for specific cancers (Gonçalves et al, 2019;Bhattacharya and Zhang, 2015;Bell et al, 2014).…”
Section: Emerging Experimental Support and Possibility Of Verification Of The Proposed Theorymentioning
confidence: 99%
“…In addition, we should observe that Oliveira et al recently reproduced the same effects obtained by Andrade et al 23 in an in vitro model, adding a mechanistic molecular explanation to the observed effects in single B16-F10 cell cultures. 31 In their study, Şeker et al 32 sought to identify continuity between the effect of taxanes as used in conventional treatment for breast cancer and the same drugs in high dilution.…”
Section: Discussionmentioning
confidence: 99%
“…Cancer-associated fibroblasts are involved in all the processes leading to physiological changes that allow cancer cells to become malignant, such as the production of extracellular matrix molecules and its remodeling, providing survival signals, and promoting cancer cell invasion and proliferation. Gonçalves and Potrich [11] used molecular biology techniques and standard functional assays to assess the changes related to the metastatic phenotype. The findings of this study indicate that these products reprogram, molecularly and functionally, melanoma cells in vitro, modulating their metastatic phenotype [11].…”
Section: Evolution Of Lesions On the Footpad Of Mice Paws Infected Wi...mentioning
confidence: 99%
“…Gonçalves and Potrich [11] used molecular biology techniques and standard functional assays to assess the changes related to the metastatic phenotype. The findings of this study indicate that these products reprogram, molecularly and functionally, melanoma cells in vitro, modulating their metastatic phenotype [11]. Guimaraes et al [12] described the results of an experimental laboratory validation of the potential of peritoneal macrophages, challenged with a complex homeopathic medication (CHM/M8), to stimulate the immune effectiveness of mesenteric lymph node lymphocytes.…”
Section: Evolution Of Lesions On the Footpad Of Mice Paws Infected Wi...mentioning
confidence: 99%